2016
DOI: 10.3329/bjp.v11i3.25731
|View full text |Cite
|
Sign up to set email alerts
|

Quinazoline pharmacophore in therapeutic medicine

Abstract: This present study comprehensively expatiates the functionalized utilization of quinazoline scaffolds in drug development and furnishes latest updates in pharmacological appositeness of its derivatives in order to reveal novel pathways for therapeutic targets. It traverses numerous biological potentials of quinazoline in the contemporary time to allow researchers' unhindered access to the beneficial role of quinazoline in fighting infectious diseases for future drug discovery. This work provides broad overview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 127 publications
(132 reference statements)
0
18
0
Order By: Relevance
“…The 1,3-diazanaphthalene, or quinazoline, structural motif is a privileged pharmacological scaffold 1 found in a wide range of bioactive compounds designed for treating health conditions including cancer, inflammation, hypertension, obesity, and infection 26 . Similarly substituted anilines are key elements of bioactive compounds 7 and valuable industrial reagents 8,9 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The 1,3-diazanaphthalene, or quinazoline, structural motif is a privileged pharmacological scaffold 1 found in a wide range of bioactive compounds designed for treating health conditions including cancer, inflammation, hypertension, obesity, and infection 26 . Similarly substituted anilines are key elements of bioactive compounds 7 and valuable industrial reagents 8,9 (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Quinazoline-2,4(1H,3H)-dione and its derivatives are important intermediates as key building blocks in the synthesis of remedial drugs for heart disease and hypertension. 6,7 They are usually prepared with toxic and environment-unfriendly reagents, such as phosgene, 8 potassium cyanate 9 and isocyanate. 10 Recently, it has been reported that quinazoline-2,4(1H,3H)-dione could be prepared via the coupling of CO 2 and 2-aminobenzonitriles.…”
Section: Introductionmentioning
confidence: 99%
“…Quinazolines and their carbonyl derivatives, namely quinazolinones, are important structural motifs present in many natural and synthetic compounds exhibiting diverse biological activities like soporific, sedative, antidiabetic, antibacterial, antifungal, anticancer, anticonvulsant, antimalarial, antiinflamatory, antiviral, etc . A list of already approved marketed drugs includes several compounds containing quinazoline pharmacophore, e.g., 6,7‐dimethoxyquinazolin‐4‐amine derivatives such as prazosin, terazosin, alfuzosin, and doxazosin .…”
Section: Introductionmentioning
confidence: 99%